Efeitos clínicos, endócrinos e metabólicos da rosiglitazona na síndrome dos ovários policísticos - Batista, José Gomes [UNIFESP] (2009)
The objectives of the present study are to evaluate the clinical, endocrine and metabolic effects of the rosiglitazone in patients with polycystic ovarian syndrome before and after twelve weeks of treatment. It was be evaluated, besides menstrual pattern and the hyperandrogenism, the hormonal profile (FSH, LH, 17 B-estradiol, total and free testosterone, 17 hydroxiprogesterone, dehudroepiandrosterone sulphate) and the seric levels of IGF-1, IGFBP-3, SHBG (globulin that links sexual hormones); examine the repercussions of cardiovascular risk (abdominal circumference, HDLs cholesterol, triglycerides, systemic arterial pressure, glycemy and insulin); verify thru transvaginal ultrasonography, the ovary blood flow and the endometrial histomorphologic aspects after treatment. The study was prospective, randomized, doubleblinded, using placebo as control. 33 patients were included and divided in two groups 1) Placebo Group (XZ), with 17 patients and 2) Rosiglitazone Group (ZX), with 16 patients, who used a capsule with 4mg, oral way, twice a day, for 12 weeks. We concluded that the treatment with rosiglitazone during three months determined: 1) improved the menstrual pattern and the symptoms and clinic signs related with hyperandrogenism; 2) a decrease in androstenedione, free testosterone and type 1 growth factor insulinoid values; 3) increase of the sexual steroids carry protein (SHBG) index; 4) improvement of the insulinic resistance, shown by the 2 hours glycemic overload; 5) a number reduction of women with metabolic syndrome and 6) the endometrium secrecy pattern got predominant. No significance variation in ovarian volume and flow were found after treatment with rosiglitazone. It’s suggested that rosiglitazone is a alternative way to correct insulinic resistance, decreasing the occurrence of the metabolic syndrome. Besides, it increases the menstrual pattern and hyperandrogenism.